2008
DOI: 10.2114/jpa2.27.309
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the Compensatory Step by the Trailing Leg Following an Unexpected Forward Slip while Walking

Abstract: In this study, we described the joint angle changes of the trailing leg during the compensatory step used to recover balance following a forward slip while walking. Fifteen healthy young males walked on a walkway which incorporated a movable platform to simulate a forward slip while walking. In 12 out of the 15 subjects, the trailing leg was rapidly lowered during the swing phase and was placed on the ground behind the slipping foot following the onset of the slip. Time taken for the onset of the slip to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Consistently, it has been suggested that the recovery limb should extend the knee joint as quickly as possible for fall prevention. 13 As older adults tend to fall due to the same cause (i.e., instability or limb-collapse), 31 leg-extension exercises and whole body vibration training, 5,28 which could increase knee extensor strength, may be helpful for individuals who tend to fall due to instability, while plantar flexion exercises and resistance training, 9,26 which could increase planter flexor strength, may be helpful for individuals who tend to fall due to limb collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, it has been suggested that the recovery limb should extend the knee joint as quickly as possible for fall prevention. 13 As older adults tend to fall due to the same cause (i.e., instability or limb-collapse), 31 leg-extension exercises and whole body vibration training, 5,28 which could increase knee extensor strength, may be helpful for individuals who tend to fall due to instability, while plantar flexion exercises and resistance training, 9,26 which could increase planter flexor strength, may be helpful for individuals who tend to fall due to limb collapse.…”
Section: Discussionmentioning
confidence: 99%
“…In the final 30% of stance phase the foot plantar flexes again to prepare for the push off phase of walking and reaches a range of 14°-20°at push off [24][25][26]. But, the vertical climbing in coconut tree requires initial dorsiflexion in stance phase (20°-36°) followed by plantar flexion (16°-51°),by push off.…”
Section: B Video Sequence Analysismentioning
confidence: 99%
“…The eight video cameras were placed around the walkway to create a capture volume. Each marker is simultaneously imaged by multiple cameras and the location of the marker in the 3D space (x, y, z coordinates) is computed using triangulation by the Vicon Nexus software.A Plug-in Gait (PIG) marker set was used for the kinematic data collection in this study.PIG is the Vicon implementation of the Conventional Gait Model which is widely used by the gait analysis community and has been validated in a number of studies(Andreoni, et al, 2009;Hwang & Kim, 2009;Riley, et al, 2007;Kojima, Nakajima, & Takada, 2008). PIG uses a defined marker set and a set of subject measurements to create joint kinematics and kinetics output.…”
mentioning
confidence: 99%